2008
DOI: 10.1111/j.1365-2958.2008.06411.x
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding protein CsrA controls cyclic di‐GMP metabolism by directly regulating the expression of GGDEF proteins

Abstract: SummaryThe carbon storage regulator CsrA is an RNA binding protein that controls carbon metabolism, biofilm formation and motility in various eubacteria. Nevertheless, in Escherichia coli only five target mRNAs have been shown to be directly regulated by CsrA at the post-transcriptional level. Here we identified two new direct targets for CsrA, ycdT and ydeH, both of which encode proteins with GGDEF domains. A csrA mutation caused mRNA levels of ycdT and ydeH to increase more than 10-fold. RNA mobility shift a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
185
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(195 citation statements)
references
References 81 publications
4
185
0
6
Order By: Relevance
“…Given that enhanced signaling and overshoot are known to be generated by negative feedback under certain conditions (1) and that native csrD was necessary for these behaviors, our findings are consistent with the reported negativefeedback regulation in which CsrA represses the production of CsrD. In further support of this, we demonstrated that enhanced signaling does not occur with the synthetic csrD gene, which lacks the flanking sequences (including the native csrD promoter and 5′-UTR sequences) that are necessary for CsrA repression of CsrD production (12,25). Instead, we found that the induction of a small, constant amount of CsrD from synthetic csrD resulted in slower signaling than in the control cascade without CsrD induction (Fig.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Given that enhanced signaling and overshoot are known to be generated by negative feedback under certain conditions (1) and that native csrD was necessary for these behaviors, our findings are consistent with the reported negativefeedback regulation in which CsrA represses the production of CsrD. In further support of this, we demonstrated that enhanced signaling does not occur with the synthetic csrD gene, which lacks the flanking sequences (including the native csrD promoter and 5′-UTR sequences) that are necessary for CsrA repression of CsrD production (12,25). Instead, we found that the induction of a small, constant amount of CsrD from synthetic csrD resulted in slower signaling than in the control cascade without CsrD induction (Fig.…”
Section: Resultssupporting
confidence: 78%
“…RT-PCR that the CsrD mRNA concentration decreases with increased CsrA production (SI Text), which is consistent with negative feedback and previous reports (12,25).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The domain requirement is reminiscent of LapD, and it is likely that c-di-GMP-driven conformational change (but not an inside-out mechanism) is associated with CsrD targeting sRNAs for RNase E-mediated degradation (149). The relationship between Csr/Rsm regulation and c-di-GMP signaling has been strengthened by the findings of CsrA regulating the expression of proteins containing the GGDEF, GGDEF-EAL, and EAL domains in E. coli and Salmonella enterica serovar Typhimurium via direct binding to the mRNA leaders of the respective genes (70,71). Although a link between Gac/Rsm regulation and cyclic-di-GMP has recently been established in P. aeruginosa, the relationship remains poorly understood in this organism.…”
Section: Noncoding Rnas Mattermentioning
confidence: 82%
“…In Escherichia coli, CsrA activates glycolysis and central carbon pathways (7)(8)(9)(10)(11)(12)(13) and motility (14,15). Conversely, it represses gluconeogenesis (7), glycogen biosynthesis (16)(17)(18)(19)(20), biofilm formation (21)(22)(23)(24), the stringent response (25), and expression of genes involved in other stress resistance and stationary-phase processes, e.g., cstA, hfq, cel, sdiA, and nhaR (24,(26)(27)(28)(29)(30). Its effects on pathogenesis are complex.…”
mentioning
confidence: 99%